Comparison of three DNA extraction methods from raw cow's milk sample - Omar, Syahirah (2020)
The progress and advancement in deoxyribonucleic acid (DNA) extraction has greatly evolved since it was initally performed in year 1986. DNA extraction has always be the first step required prior to any DNA analysis. In this study, raw cow’s milk has been subjected to three different extraction methods for determining the method that perform best in terms of DNA yield. Genomic DNA extracted from raw cow’s milk sample by the three methods was evaluated for purity and quantity by spectrophotometry and gel electrophoresis. On average, all three methods statistically showed no significant differences on final results of nucleic acid concentration, however, in terms of cost-effectiveness, conventional methods of phenol-chloroform and TENS method saved more compared to commercial kit. The results of this study showed that phenol-chloroform method had the best DNA yield based on the Nanodrop spectrophotometer measurement, followed by TENS method and commercial kit.